2016
DOI: 10.1007/s12020-016-0952-3
|View full text |Cite
|
Sign up to set email alerts
|

New insights for male infertility revealed by alterations in spermatic function and differential testicular expression of thyroid-related genes

Abstract: The impact of thyroid hormone (TH) disorders on male reproductive biology has been a controversial issue for many years. Recently, we reported that hypothyroid male rats have a disruption of the seminiferous epithelium, which may compromise spermatogenesis. To improve the understanding of the reproductive pathogenesis of hypothyroidism and hyperthyroidism, male Wistar rats that developed these dysfunctions in adulthood were used as an experimental model. We evaluated the sperm production, reserves, transit tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 56 publications
2
34
0
2
Order By: Relevance
“…Others have reported on the negative effects of hypothyroidism on male reproductive function (7,26), and particularly on sperm concentration, motility, and morphology (27,28). Similar observations have been made in animal models (29). Very few studies, however, have focused on the effects of SCH on male reproduction.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Others have reported on the negative effects of hypothyroidism on male reproductive function (7,26), and particularly on sperm concentration, motility, and morphology (27,28). Similar observations have been made in animal models (29). Very few studies, however, have focused on the effects of SCH on male reproduction.…”
Section: Discussionsupporting
confidence: 75%
“…As only a few studies have delineated the mechanistic links between thyroid dysfunction and spermatogenesis, we put forward the following proposals that might help explain the issues. First, animal studies have indicated that a hypothyroid state can affect sperm function (29). An increase in reactive oxygen species production was also observed in sperm isolated from hypothyroid animal models (33).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the thyroid hormones (THs), 3,5,3′-triiodothyronine (T 3 ) and thyroxine (T 4 ) impact the reproductive function, and thyroid dysfunction is associated with an adverse effect on fertility, both in men [1,2] and women [3]. Indeed, hyperthyroidism or thyrotoxicosis damages spermatogenesis causing maturation arrest, impairs mitochondrial activity and alters the antioxidant systems in rats [4]. Hyperthyroidism results in asthenozoospermia in humans [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…5 It reduces serum testosterone levels and is associated with hypogonadism and sperm morphological abnormalities. 4,7 More recent studies, however, have shown that hypothyroidism causes decreased total testosterone (TT) and "sex hormone binding globulin (SHBG)" levels, whereas "luteinizing hormone (LH)"…”
mentioning
confidence: 99%